2009
DOI: 10.1111/j.1439-037x.2008.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deficit Drip Irrigation Ratios on Cotton (Gossypium hirsutum L.) Yield and Fibre Quality

Abstract: Increasing irrigation costs and declining water availability compel producers to adapt irrigation strategies for maximum crop yield and water use efficiency. A field trial was conducted to observe the effects of various drip irrigation ratios (IR‐0, IR‐25, IR‐50, IR‐75 and IR‐100) on water use efficiency (WUE), the irrigation water use efficiency (IWUE), lint yield, yield components and fibre quality at two upland cotton varieties during 2004 and 2005. WUE was found to increase from 0.62 to 0.71 kg m−3 as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
95
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 36 publications
29
95
1
5
Order By: Relevance
“…Cotton responses to deficit irrigation have been reported in some earlier works (Wanjura et al, 2002;Howell et al, 2004;Pettigrew, 2004;Dagdelen et al, 2006;DeTar, 2008;Basal et al, 2009). When adopting deficit irrigation, it is difficult to predict the yield re-Simulating cotton response to deficit irrigation with AquaCrop minimum and maximum temperature, dew point, wind velocity at 2 m, solar radiation, and rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton responses to deficit irrigation have been reported in some earlier works (Wanjura et al, 2002;Howell et al, 2004;Pettigrew, 2004;Dagdelen et al, 2006;DeTar, 2008;Basal et al, 2009). When adopting deficit irrigation, it is difficult to predict the yield re-Simulating cotton response to deficit irrigation with AquaCrop minimum and maximum temperature, dew point, wind velocity at 2 m, solar radiation, and rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…High fiber quality is essential for textile industry because it affects the quality of final products and the processing performance, with impact on processing cost and branding/marketing of the products (Basal et al, 2009a). ISSN 2166-0379 2017 In cotton, the effect of GxE varies among fiber traits, which means that certain fiber traits are more sensitive to environmental changes than others.…”
Section: Discussionmentioning
confidence: 99%
“…Fiber quality is a complex of various traits, such as fiber length, strength, uniformity etc. (Poehlman and Sleper, 1995) and thus it depends on both genetic and environmental factors that influence the plant's development (Bradow and Davidonis, 2000;Campbell and Jones, 2005;Basal et al, 2009a;Kothari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that irrigation improved ginning percentage and increased yield, and the fiber quality parameters such as the length, micronaire, and uniformity were affected by the irrigation regimes. In a research by Basal Dagdelen, Unay, and Yilmaz (2009), it was showed that deficit irrigation of cotton with drip irrigation at 75% level did not decrease seed cotton yield and there was no significant differences in fiber length, fineness, uniformity, and elongation between the 100% and 75% irrigation levels. Whitaker, Ritchie, Bednarz, and Mills (2008) reported that non-irrigated cotton matured earlier than the irrigated.…”
Section: Introductionmentioning
confidence: 97%